2021
DOI: 10.3928/23258160-20210429-03
|View full text |Cite
|
Sign up to set email alerts
|

Rhegmatogenous Retinal Detachment in the Setting of Endophthalmitis: Risk Factors and Visual Outcomes

Abstract: BACKGROUND AND OBJECTIVE: To investigate risk factors for rhegmatogenous retinal detachment (RRD) and visual acuity (VA) in eyes with RRD after developing endophthalmitis. PATIENTS AND METHODS: Retrospective comparative study of 133 eyes with endophthalmitis at a tertiary center between 2009 and 2018. Demographics, exam findings, interventions, and outcomes were assessed. Cases of RRD within 6 months after onset of endophthalmitis were further analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…14 In groups 1 and 2 of our study, VA improved in 26 patients (34.21%) and 16 patients (35.55%), respectively. Although there was no statistically significant difference between the two, the final VA in group 1 (20/1291) was noted to 12 The majority of detachments in both groups in this study were noted to be due to atrophic holes. This reemphasizes the importance of a thorough peripheral retinal evaluation in follow-up cases with endophthalmitis and during the primary vitrectomy itself, if possible.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…14 In groups 1 and 2 of our study, VA improved in 26 patients (34.21%) and 16 patients (35.55%), respectively. Although there was no statistically significant difference between the two, the final VA in group 1 (20/1291) was noted to 12 The majority of detachments in both groups in this study were noted to be due to atrophic holes. This reemphasizes the importance of a thorough peripheral retinal evaluation in follow-up cases with endophthalmitis and during the primary vitrectomy itself, if possible.…”
Section: Discussioncontrasting
confidence: 59%
“…Previous studies have reported a bimodal peak with two predominant presentations in either the third decade or the sixth decade. 3,6,[9][10][11][12] The etiology of endophthalmitis in both of our groups was found to be exogenous in >80% of the study patients. While cataract surgery and trauma was noted as the most common etiology for exogenous endophthalmitis in group 1, cataract surgery alone was the predominant etiology in group 2.…”
Section: Discussionmentioning
confidence: 61%
“…5 Chiquet et al, Wang et al, and Lee et al also did not report any relationship between organisms and RD rates. 6,11,20 In this review, 21 (66%) of the RD cases occurred within the first month after endophthalmitis diagnosis. This is comparable with the 56% in the investigation of Chiquet et al The rate of RD managed surgically was 94%, similar to that in Chiquet et al (93%) yet higher than in EVS (44%).…”
Section: Discussionmentioning
confidence: 83%
“…5 Chiquet et al, Wang et al, and Lee et al also did not report any relationship between organisms and RD rates. 6,11,20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation